Acute exacerbation of idiopathic pulmonary fibrosis: application of the diagnostic criteria and the role of respiratory intermediate care unit and mechanical ventilation - Barbosa, Joana Daniela Rodrigues; Salgado, Sara Moreira da Silva; Esteves, Maria Paula Cruz Mata Nazaré Pinheiro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Acute exacerbations of Idiopathic Pulmonary Fibrosis (AE-IPF) have a poor prognosis, and the majority of evidence supports the lack of benefit of invasive mechanical ventilation. The objective was to evaluate patients with AE-IPF admitted to a Respiratory Intermediate Care Unit (RICU). Methods: A retrospective study was conducted on AE-IPF patients admitted to a Portuguese RICU from 2014 to 2018. Results: Thirty-one admissions (n=20) corresponded to IPF (9 were suspected AE by the diagnostic criteria of IPFnet 2007 and 15 by the International Working Group Report 2016). The mean age was 70±11 years, and 53% were male. FVC was 69.7±29% and DLCO was 38.7±14%. The initial PaO2/FiO2 was 145±71, as opposed to 228±91 in non-AE patients. Bronchoscopy was performed on three patients. Regarding treatment, 60% had non-invasive ventilation, and 40% had high-flow oxygen therapy. Methylprednisolone pulses were used in two patients. Eight patients died during hospitalization (53%); four died within five months, and only one survived. Conclusions: Recent diagnostic criteria of AE-IPF help identify these patients, contrary to old criteria. Bronchoscopy is not always possible to perform, and a small number of patients receive methylprednisolone pulses. No statistically significant differences were observed between the discharged and deceased groups, but higher levels of LDH at admission and lower DLCO could help identify risk groups. AE-IPF has a poor prognosis, and admission at RICU could be helpful in the management of these patients, reducing the need for admission to intensive care units, and consequently costs and risks of invasive mechanical ventilation.